Spatial and Seasonal Variations in the Stable Isotope Values and Trophic Positions of Dominant Zooplankton Groups in Jiaozhou Bay, China - Zhixin Ke; Zhixin Ke; Zhixin Ke; Ruofei Li; Ruofei Li; Danting Chen; Chunyu Zhao; Yehui Tan; Yehui Tan; Yehui Tan (Frontiers in Marine Science, 2022)
The spatial and seasonal distributions of stable carbon and nitrogen isotopes (δ13C and δ15N) in dominant zooplankton groups were investigated in Jiaozhou Bay. Zooplankton δ13C values ranged from −22.89‰ to −15.86‰, and δ15N values ranged from 3.18‰ to 13.57‰, respectively. The δ13C and δ15N values generally followed the order of small zooplankton < large calanoids < small Sagitta < large Sagitta. Spatial distribution patterns of zooplankton δ13C and δ15N values varied in different seasons. Our results suggested that the spatial variation of δ13C was mainly controlled by terrigenous organic matter (OM) input and phytoplankton biomass, but water temperature may have played a key role in the seasonal variation of δ13C. In spring, the high phytoplankton biomass might increase the δ13C value of small zooplankton in the inner bay. During other seasons, the δ13C values of zooplankton generally increased from the inner bay to the outer bay, which might be associated with the influence of 13C-depleted terrigenous OM carried by the river discharge. Small zooplankton stable isotope values were significantly correlated with that of particulate organic matter (POM). The influence of anthropogenic nutrient input on isotopic baseline can be cascaded to the zooplankton, and the effect might be weak at higher trophic levels. The Bayesian standard ellipse areas of dominant zooplankton groups were generally smallest in the winter, suggesting a narrow niche width during that time. The niche partition between small zooplankton, large calanoids, and Sagitta was most distinct in winter, and followed by summer. The relative trophic level of Sagitta ranged from 2.23 to 4.01, which generally declined from the inner bay to the outer bay during the spring, autumn, and winter seasons. High anthropogenic nutrient loading might reduce the difference in trophic niches among zooplankton groups. This study provided detailed information on the distribution of zooplankton δ13C and δ15N in a coastal bay, which will be useful for understanding the anthropogenic influence on the ecosystem structure and function.